Gambaran Kejadian Computer Vision Syndrome dan Faktor Risikonya pada Mahasiswa FKM UI di Masa Pandemi Covid-19 - Shadik, Rahadian Muhamad; Widanarko, Baiduri (National Journal of Occupational Health and Safety, 2023)
Due to the Covid-19 pandemic, many activities that were previously carried out offline have turned into online, including the education sector. This condition increased the use duration of electronic devices with digital screens/VDT, especially among students. It is one of the risk factors for Computer Vision Syndrome. Apart from duration, several risk factors are also associated with Computer Vision Syndrome. The aims of this study are to see an overview of Computer Vision Syndrome incidence and analyze the relationship between Computer Vision Syndrome incidence and its risk factors in regular (S1) and postgraduate (S2) students, FKM UI during the Covid-19 pandemic. This research was conducted in March-June 2022 using the CVS-Q questionnaire and several short questions related to risk factors distributed online. The study design used in this study was cross-sectional and involved 250 respondents from regular undergraduate and postgraduate students of FKM UI. The results of this study indicate that there are 6 variables that have a significant relationship, namely age (P 0.000), duration of use of digital screens/VDT (P=0.006), rest pattern (P=0.007), eye refraction abnormalities (P=0.014), use of antiglare (P=0.011), and Screen brightness (P=0.030). Therefore, further controls and interventions are needed so that these problems can be overcome.